1, 3-Dinitrobenze-Induced Genotoxicity Through Altering Nuclear Integrity of Diploid and Polyploidy Germ Cells. Issue 3 (20th September 2019) - Peiris, L. Dinithi C.; Chathu, Prathitha; Perera, D. D. B. D.; Moore, Harry D.
1, 3-Dinitrobenzene (mDNB) is a widely used intermediate in commercial products and causes testicular injury. However, genotoxic effects upon low-level exposure are poorly understood. The present study evaluated the effects of very low-chronic doses of mDNB on sperm nuclear integrity. Male hamsters were treated with 1.5 mg/kg/d/4 wks (group A), 1.5 mg/kg/mDNB/d/week/4 weeks (group B), 1.0 mg/kg/mDNB/3 d/wk/4 wks (group C), or polyethylene glycol 600 (control). Nuclear integrity of distal cauda epididymal sperm was determined using the sperm chromatin structure assay and acridine orange staining (AOS). The germ cell nuclear integrity was assessed by the comet assay. Testicular histopathology was conducted to evaluate the sensitive stages. The comet assay revealed denatured nuclear DNA in group A (in diploid and polyploid cells from weeks 2-5); respectively at week 4 and weeks 3 to 4 in groups B and C. According to AOS, only group A animals exhibited denatured sperm DNA (weeks 1 and 3). The effective sperm count declined from weeks 1 to 6. Mean sperm DNA denaturation extent, percentage cells outside the main population, and standard deviation indicated altered sperm nuclear integrity in group A. Same animals exhibited progressive disruption of the Sertoli cells, while groups B and C exhibited damages on germ cells. The results suggest that mDNB affects sperm nuclear integrity at very low chronic doses targeting cell-specific testicular damage.